Cytotoxic and immune‐mediated killing of human colorectal cancer by reovirus‐loaded blood and liver mononuclear cells1. Issue 10 (26th November 2012) - Adair, Robert A.; Scott, Karen J.; Fraser, Sheila; Errington‐Mais, Fiona; Pandha, Hardev; Coffey, Matt; Selby, Peter; Cook, Graham P.; Vile, Richard; Harrington, Kevin J.; Toogood, Giles; Melcher, Alan A.
Abstract Reovirus is a promising oncolytic virus, acting by both direct and immune‐mediated mechanisms, although its potential may be limited by inactivation after systemic delivery. Our study addressed whether systemically delivered reovirus might be shielded from neutralising antibodies by cell carriage and whether virus‐loaded blood or hepatic innate immune effector cells become activated to kill colorectal cancer cells metastatic to the liver in human systems. We found that reovirus was directly cytotoxic against tumour cells but not against fresh hepatocytes. Although direct tumour cell killing by neat virus was significantly reduced in the presence of neutralising serum, reovirus was protected when loaded onto peripheral blood mononuclear cells, which may carry virus after intravenous administration in patients. As well as handing off virus for direct oncolytic killing, natural killer (NK) cells within reovirus‐treated blood mononuclear cells were stimulated to kill tumour targets, but not normal hepatocytes, in a Type I interferon‐dependent manner. Similarly, NK cells within liver mononuclear cells became selectively cytotoxic towards tumour cells when activated by reovirus. Hence, intravenous reovirus may evade neutralisation by serum via binding to circulating mononuclear cells, and this blood cell carriage has the potential to investigate both direct and innate immune‐mediated therapy against human colorectal or other cancers metastatic to the liver.